Cell type-specific changes in Wnt signaling and neuronal differentiation in the developing mouse cortex after prenatal alcohol exposure during neurogenesis - Sambo, Danielle; Gohel, Chiraag; Yuan, Qiaoping; Sukumar, Gauthaman; Alba, Camille; Dalgard, Clifton L.; Goldman, David (Frontiers in Cell and Developmental Biology, 2022)
Fetal Alcohol Spectrum Disorder (FASD) encompasses an array of effects of prenatal alcohol exposure (PAE), including physical abnormalities and cognitive and behavioral deficits. Disruptions of cortical development have been implicated in multiple PAE studies, with deficits including decreased progenitor proliferation, disrupted neuronal differentiation, aberrant radial migration of pyramidal neurons, and decreased cortical thickness. While several mechanisms of alcohol teratogenicity have been explored, how specific cell types in the brain at different developmental time points may be differentially affected by PAE is still poorly understood. In this study, we used single nucleus RNA sequencing (snRNAseq) to investigate whether moderate PAE from neurulation through peak cortical neurogenesis induces cell type-specific transcriptomic changes in the developing murine brain. Cluster analysis identified 25 neuronal cell types, including subtypes of radial glial cells (RGCs), intermediate progenitor cells (IPCs), projection neurons, and interneurons. Only Wnt-expressing cortical hem RGCs showed a significant decrease in the percentage of cells after PAE, with no cell types showing PAE-induced apoptosis as measured by caspase expression. Cell cycle analysis revealed only a subtype of RGCs expressing the downstream Wnt signaling transcription factor Tcf7l2 had a decreased percentage of cells in the G2/M phase of the cell cycle, suggesting decreased proliferation in this RGC subtype and further implicating disrupted Wnt signaling after PAE at this early developmental timepoint. An increased pseudotime score in IPC and projection neuron cell types indicated that PAE led to increased or premature differentiation of these cells. Biological processes affected by PAE included the upregulation of pathways related to synaptic activity and neuronal differentiation and downregulation of pathways related to chromosome structure and the cell cycle. Several cell types showed a decrease in Wnt signaling pathways, with several genes related to Wnt signaling altered by PAE in multiple cell types. As Wnt has been shown to promote proliferation and inhibit differentiation at earlier stages in development, the downregulation of Wnt signaling may have resulted in premature neuronal maturation of projection neurons and their intermediate progenitors. Overall, these findings provide further insight into the cell type-specific effects of PAE during early corticogenesis.